2020
DOI: 10.1007/s00204-020-02927-8
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibition in electric eel and human donor blood: an in vitro approach to investigate interspecies differences and human variability in toxicodynamics

Abstract: In chemical risk assessment, default uncertainty factors are used to account for interspecies and interindividual differences, and differences in toxicokinetics and toxicodynamics herein. However, these default factors come with little scientific support. Therefore, our aim was to develop an in vitro method, using acetylcholinesterase (AChE) inhibition as a proof of principle, to assess both interspecies and interindividual differences in toxicodynamics. Electric eel enzyme and human blood of 20 different dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
3
23
0
Order By: Relevance
“…Serum creatinine, uric acid, and urea indicators of kidney function increased significantly in rats after CPF treatment which may indicate degradation of both purines and pyrimidines and impaired kidney function. Many reports investigated an increase of creatinine, urea and uric acid in serum of rats exposed to toxic compounds including pesticides ( Badraoui et al, 2007 , 2012 ; Hakim et al, 2008 ; Amri et al, 2017 ; Meligi and Hassan, 2017 ; Kasteel et al, 2020 ). Levels of serum cholesterol, triglycerides, LDL, and glucose were statistically enhanced in rats exposed to CPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum creatinine, uric acid, and urea indicators of kidney function increased significantly in rats after CPF treatment which may indicate degradation of both purines and pyrimidines and impaired kidney function. Many reports investigated an increase of creatinine, urea and uric acid in serum of rats exposed to toxic compounds including pesticides ( Badraoui et al, 2007 , 2012 ; Hakim et al, 2008 ; Amri et al, 2017 ; Meligi and Hassan, 2017 ; Kasteel et al, 2020 ). Levels of serum cholesterol, triglycerides, LDL, and glucose were statistically enhanced in rats exposed to CPF.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are in accordance with those of Mosbah et al (2016) who demonstrated a significant increase in LPO level and decreases of SOD, CAT, and GPx activities in plasma and testis after treatment of male rats with CPF. In fact, CPF can be responsible for increasing the production of reactive oxygen species (ROS) in cells, which lead to increased lipid peroxidation levels and oxidative damage ( Kasteel et al, 2020 ). The decrease in antioxidant enzyme activities in liver and kidney tissues was due to cellular injury and death of healthy cells that are able to respond to the oxidative insult.…”
Section: Discussionmentioning
confidence: 99%
“…One would expect that effect concentrations would decrease with longer incubation times until 100% of the binding sites is inhibited, as shown before by Aurbek et al ( 2006 ) and Krstić et al ( 2008 ). With a relatively long pre-incubation time of 15 min as we have used in the present study, similar to incubation times previously applied by other research groups (e.g., Aurbek et al 2006 ; Kasteel et al 2020 ), we aimed to obtain a relevant and conservative estimation of the effect concentrations, as also indicated by the small difference between the BMDL 10 value obtained with our predicted rat dose–response data and the BMDL 10 value from a reported in vivo study in rats.…”
Section: Discussionmentioning
confidence: 84%
“…Electric eel enzyme and human blood of 20 different donors (12 men/8 women) were exposed to eight different compounds (chlorpyrifos, chlorpyrifos-oxon, phosmet, phosmet-oxon, diazinon, diazinon-oxon, pirimicarb, rivastigmine) and inhibition of AChE was measured using the Ellman method. The methods are described in detail in the accompanying publication (Kasteel et al, 2020b). The present document has been produced and adopted by the bodies identified above as authors.…”
Section: Neurotoxicants: Acetylcholinesterase-inhibiting Chemicalsmentioning
confidence: 99%
“…In all, this study provides a reliable in vitro method for assessing human variability in AChE toxicodynamics. The data suggest that the default uncertainty factor of ~3.16 may overestimate human variability for this toxicity endpoint, implying that specific toxicodynamicrelated adjustment factors can support quantitative in vitro to in vivo extrapolations that link kinetic and dynamic data in order to improve chemical risk assessment (Kasteel et al, 2020b). Measured IC50s and IC20s are reported in Table 27 for both electric eel and human AChE.…”
Section: Acetylcholine-inhibiting Compoundsmentioning
confidence: 99%